Good Work is a Good Solution - Abdunabi Toychiev; Ph.D. Karimov B.N (Genius Journals, 2022)
Literature has a wide range of possibilities in shaping the level of members of society. Coverage of social activities, emotions, and thoughts of an individual becomes one of the main tasks of literature. In this sense, the study and investigation of the essence of the works created and being created nowadays is one of the most important tasks. In particular, the relevance of the topic determines the role of Nurali Kabul’s creativity in Uzbek prose, the factors of the origin of his works, development processes, features, artistic details, types, functions, teaching, research of his wealth, problems related to the question of style and skill are not studied in a systematic holistic monographic plan. Naturally, the study of problems related to the artistic features of the works of the writer Nurali Kabul, which we have laid the basis for the study, is of particular importance in the science of Uzbek literature
Keywords: Literary work; environment; hero; Oyqor